An Analysis of Impoliteness Strategy Used by The Main Character in "A Man Called Otto" Movie - Khaqqi, Achmad Amirul; Bramantya Pradipta (Proceeding of Undergraduate Conference on Literature, Linguistic, and Cultural Studies, 2024)
This research aims to identify and analysis the types and functions of impoliteness strategies used by the main character in A Man Called Otto movie. This research utilized a descriptive qualitative method. The data consisted of utterances, specifically used by the main character, Otto. The source of the data for this research is A Man Called Otto movie with helps by the transcripts to ensure that utterances in the movie are completely and accurately delivered. The researcher applied Culpeper’s theory of impoliteness strategy (2005) and its functions (2011). The results showed that 63 impoliteness strategies were found: bald on-record (11) utterances, positive impoliteness (20) utterances, negative impoliteness (23) utterances, off-record (1) utterance, and withhold politeness (8) utterances. Negative impoliteness more inclined because Otto’s characteristic is shaped by profound loneliness after his wife's death, making him impatient, straightforward, and irritable. Furthermore, two out of three functions occur in this research, namely affective impoliteness (25) utterances and coercive functions (38) utterances, coercive impoliteness more inclined because Otto’s desire to gain an advantage or maintain control in the situation, coupled with his power dynamic such as being older and more experienced. Furthermore, entertaining function was not found in this movie because it focuses about Otto’s personal journey and emotional challenges.